Determinan Kebersihan Diri Saat Menstruasi Pada Remaja Putri SMP Kristen Waimangura Sumba Barat Daya Tahun 2022 - Jhaney Clarancia Martcelina Bili (Jurnal Keperawatan Muhammadiyah, 2023)
Menstruation is a natural process that marks the phase of puberty in young women. Personal hygiene during menstruation plays an important role in a person's health status, especially avoiding disturbances in the functioning of the reproductive apparatus. During menstruation, blood vessels in the uterus are very easily infected, because germs are easier to enter, infections that occur can cause various diseases of the reproductive apparatus. Therefore, young women should take care of and apply proper personal hygiene during menstruation. This type of research is analytical observational with a cross sectional design. The results showed that variables that had a relationship with personal hygiene measures during menstruation in young women of Waimangura Christian Junior High School included attitudes (P-value = 0.016), availability of facilities (P-value = 0.036), and maternal support (P-value = 0.0). Meanwhile, the variable that has no relationship with personal hygiene measures during menstruation in young women of Waimangura Christian Junior High School is knowledge (P-value = 0.220).